Microbioloogical Evaluation and Keeping Quality of Fishes Rered in Livestock Sewage Fed Ponds Without Artificial Feed. - BACHHIL, V N (Fishery Technology, 2017)
Livestock sewage has been utilized for fish culture. There is lack of informationon microbiolo tical evaluation and keeping quality of these fishes: This paper reveals the incidence, types of micro-organisms and keeping quality of fishes reared in livestock sewage fed ponds without artificial feed. These fishes revealed microbial incidence and keeping quality comparable to other fishes. Initial mesophilic and psychrophilic counts varied from 3.38 to 5.56 and 2.47 to 4.74. On an average, the counts reduced by about 40 % after evisceration and washing. Whole as well as washed fishes had refrigerated (8 ± 1°C) life of not more than 4 days. The average psychrophilic and mesophilic counts of ice (0 to 1°C) stored whole fishes upto 10th day varied from 3.66 to 4.81, 4.61 to 5.24 and in eviscerated and washed fishes 2.17 to 3.69 and 2.78 to 4.41.oth remained acceptable till the 10th day. Qualitative study of surface slime and gills revealed presence of Aerobacter (Enterobacter), Aeronionas, Alcaligenes, Bacillus, Clostridia, E. coli, Klebsiella, Micrococci, roteus and seudomonas.